Some generalized three-term conjugate gradient methods based on CD approach for unconstrained optimization problems - Arman, Ladan; Xu, Yuanming; Liping, Long (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Abstract In this paper, based on the efficient Conjugate Descent (CD) method, two generalized CD algorithms are proposed to solve the unconstrained optimization problems. These methods are three-term conjugate gradient methods which the generated directions by using the conjugate gradient parameters and independent of the line search satisfy in the sufficient descent condition. Furthermore, under the strong Wolfe line search, the global convergence of the proposed methods are proved. Also, the preliminary numerical results on the CUTEst collection are presented to show effectiveness of our methods.